JURIDICAL REVIEW OF COPYRIGHT INFRINGEMENT IN BOOK CIRCULATION THROUGH E-COMMERCE PLATFORMS - Hardiyanti, Vivi; Syahriar, Irman; Khairunnisah (Awang Long Law Review, 2025)
People often copy and duplicate literature since it has gotten ingrained in their minds and they don't consider the inadequacies of others. Individual copyright protection is almost nonexistent in Indonesia. Traditionally, everything created by the community is referred to as common property. The requirement for legal protection becomes apparent after the work's economic worth is established. The traditional perspective is that copyright's benefits outweigh its costs. The method used in this study relies on library resources, namely those that provide new or current scientific information or fresh perspectives on established facts or concepts. In this instance, these resources include books, journals, dissertations, theses, and other legal papers. Both primary and secondary legal sources are thoroughly used in this normative legal study. In Indonesia, copyright violations on e-commerce sites are still seen as ineffectual. Practice on the ground demonstrates that numerous copyright infringements, such as the selling of pirated books, are nevertheless widespread even though the UUHC provide a legal foundation for combating infringement. This is caused by a number of things, such as a lack of government control and e-commerce platforms' incapacity to efficiently monitor and eliminate material that violates copyright. The prior legislation was improved upon with the enactment of the UUHC (Copyright Act) of 2014. Better protection for artists and their works is undoubtedly the goal of this change. The need for more protection and legal clarity for authors, copyright holders, and owners of associated rights is heightened by the rapid advancements in science, technology, literature, and the arts. Indonesia is encouraged to further implement copyright and associated rights in its domestic legal system by its involvement in several international treaties, which enables its authors to compete globally. This is also part of the history of how UUHC 2014 came to be, superseding Act No. 19 of 2002 on Copyright.